Primary microRNA transcripts are processed co-transcriptionally. - Morlando, M; Ballarino, M; Gromak, N; Pagano, F; Bozzoni, I; Proudfoot, N (2008)
microRNAs (miRNAs) are generated from long primary (pri-) RNA polymerase II (Pol II)-derived transcripts by two RNase III processing reactions: Drosha cleavage of nuclear pri-miRNAs and Dicer cleavage of cytoplasmic pre-miRNAs. Here we show that Drosha cleavage occurs during transcription acting on both independently transcribed and intron-encoded miRNAs. We also show that both 5'-3' and 3'-5' exonucleases associate with the sites where co-transcriptional Drosha cleavage occurs, promoting intron degradation before splicing. We finally demonstrate that miRNAs can also derive from 3; flanking transcripts of Pol II genes. Our results demonstrate that multiple miRNA-containing transcripts are co-transcriptionally cleaved during their synthesis and suggest that exonucleolytic degradation from Drosha cleavage sites in pre-mRNAs may influence the splicing and maturation of numerous mRNAs.